A user equilibrium model for electric vehicles: Joint traffic and energy demand assignment. (1st May 2020) - Ferro, G.; Minciardi, R.; Robba, M.
Abstract: The development of policies for sustainable development has led to an increase in electric vehicles (EVs). This has given rise to new problems, such as the location and sizing of charging stations over the considered traffic network. The solution of such problems requires the application of analysis techniques in order to predict the joint allocation of transportation and energy demands. In this paper, an approach is proposed that extends the User Equilibrium (UE) principle in order to determine, besides to the flow over the network links, the service requests from the drivers to the various service stations. The application of this method is preliminary for the statement of any problem related to the optimization of location and sizing of service stations. The proposed approach is applied to a case study in Genoa Municipality (Liguria Region). Highlights: A new model for charging stations and electric vehicles. Traffic assignment and energy demands assessment. User Equilibrium (UE) principle for the case of electric vehicles. A real case study is considered.